Does it make any sense to fit cochlear implants according to the anatomy-based fitting? Our experience with the first series of patients - Lassaletta, Luis; Calvino, Miryam; Sánchez-Cuadrado, Isabel; Gavilán, Javier (Frontiers in Audiology and Otology, 2023)
Introduction: Personalization of treatment is a growing trend in various fields of medicine, and this includes cochlear implantation. Both the precise choice of the length and shape of the electrode array to fit a particular cochlear anatomy, as well as an individualized fitting setting have been suggested to improve hearing outcomes with a cochlear implant (CI).The aim of this study was to compare anatomy-based fitting (ABF) vs default fitting in terms of frequency-to-place mismatch, speech discrimination, and subjective outcomes in MED-EL CI users.Methods: Eight adult CI users implanted with a Synchrony ST Flex28 were enrolled prospectively. Insertion depth and tonotopic distribution of each electrode was calculated using the Otoplan software. The mismatch was calculated for each fitting strategy relative to the electrodes' tonotopic place-frequency. Speech tests and patient preference was evaluated after nine months with ABF and one month after default fitting.Results: Median angular insertion of the most apical active electrode was 594º (interquartile range 143º). ABF showed lower mismatches than default fitting in all patients (p≤0.01). Mean speech discrimination score with ABF and default fitting was 73±11% and 72±16%, respectively (p=0.672). Mean speech reception threshold with ABF and default fitting was 3.6±3.4 dB and 4.2±5.0 dB, respectively (p=0.401). All patients except one preferred ABF when they were asked about their preference.ABF maps have a lower frequency-to-place mismatch than default fitting maps. In spite of similar hearing outcomes most patients prefer ABF. More data are necessary to corroborate the benefit of the ABF over default fitting in speech and subjective tests.